Computational approach to grain boundary segregation engineering of nickel-base superalloys - Haruna Uruchida; Yuhki Tsukada; Yusuke Matsuoka; Toshiyuki Koyama (Scientific Reports)
Abstract Grain boundary (GB) strengthening elements, such as B, C, and Zr have been added in small amounts to nickel-base superalloys. However, their strengthening effects have not been quantified and no specific design principles for GB chemistry have been reported. In this study, we propose a practical computational approach for the GB segregation engineering of nickel-base superalloys. Considering the partitioning of alloying elements into coexisting phases (strengthening phases, carbides, etc.), the equilibrium composition of a high-angle GB was computed for several nickel-base superalloys using a calculation of phase diagrams database. The computational results showed that B and Mo were enriched at the GB in most of the investigated alloys. The creep rupture strengths of the investigated alloys were predicted using the computed GB composition as a regression model feature. The regression coefficients for the features confirm that B segregation at the GB has a non-negligible strengthening effect on nickel-base superalloys.